Meta-análise do tratamento de dejetos suínos em reatores anaeróbio de fluxo ascendente com manta de lodo e reator sequencial em batelada - Garcia, Gerson Guarez (2011)
The study was performed in order to evaluate, through meta-analysis, the relationship of upflow anaerobic sludge blanket or sequencing batch reactors on the removal efficiency ofpollutant loadin swine waste treatment. The database totaled 76 articles published between 1987 and 2011. The meta-analysis followed three sequential analyses: graphical, correlation and variance-covariance. Field work methodologies were used in 49% of the studies included in the databaseand bench-level experiments were used in 51% of the database papers. The share of papers with field work was 42% of studies with SBR reactor and 58% of studies with UASB reactors. The SBR reactor showed higher efficiency than the UASB reactor for removal of total solids 26% (P<0.001), total suspended solids 12%(P<0.001) and fixed suspended solids 54% (P<0.05). The removal efficiency of volatile suspended solids volatile suspended solids did not differ (P>0.05) between SBR and UASB reactors. The removal efficiency of total chemical oxygen demand (COD) was 21%higher (P<0.001) in the SBR reactors in relation to the UASB reactors. For removal of dissolved COD, the SBR reactor showed efficiency 6% higher (P<0.05) compared to the UASB reactor. The biological oxygen demand (BOD) was also more efficiently eliminated (P<0.001) by SBR reactor. The difference between reactor types for the removal efficiency of this variable was 44%. The variation in pH between the influent and effluent was 45% higher (P<0.05) in the USBA in relation to the SBR. The SBR reactor showed higher efficiency 74% (P<0.001) than the UASB reactor for the removal of total nitrogen. Likewise, the SBR reactors were 71% more efficient (P<0.01) for the total P removal. SBR reactor present higher N and P removal efficiencies in the swine waste treatment. In addition, the removal of BOD and COD is more efficient in sequential batch reactors, both in laboratory or real scale trials.